2020
DOI: 10.3390/met10091139
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development in Beta Titanium Alloys for Biomedical Applications

Abstract: β-type titanium (Ti) alloys have attracted a lot of attention as novel biomedical materials in the past decades due to their low elastic moduli and good biocompatibility. This article provides a broad and extensive review of β-type Ti alloys in terms of alloy design, preparation methods, mechanical properties, corrosion behavior, and biocompatibility. After briefly introducing the development of Ti and Ti alloys for biomedical applications, this article reviews the design of β-type Ti alloys from the perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 206 publications
(107 citation statements)
references
References 228 publications
(340 reference statements)
0
79
0
1
Order By: Relevance
“…Under a synergistic effect of the dispersion strengthening and the change in the microstructure, the hardness of RE-NW35 coating is therefore significantly enhanced. Such a phenomenon is frequently observed in the metallic materials [66][67][68][69][70][71]. Furthermore, it is interesting that the hardness of the substrate increases from 240 ± 10 to 560 ± 11 HV after remelting.…”
Section: Microstructure Featuresmentioning
confidence: 73%
“…Under a synergistic effect of the dispersion strengthening and the change in the microstructure, the hardness of RE-NW35 coating is therefore significantly enhanced. Such a phenomenon is frequently observed in the metallic materials [66][67][68][69][70][71]. Furthermore, it is interesting that the hardness of the substrate increases from 240 ± 10 to 560 ± 11 HV after remelting.…”
Section: Microstructure Featuresmentioning
confidence: 73%
“…Other research groups [179] proposed the fabrication of Ti-10Mo-xFe scaffolds using a powder metallurgy process as the potentially low-cost process to manufacture porous structure. The addition of Fe and Mo to Ti alloys enhanced their mechanical strength and reduced their elastic modulus [158,165]. The studies indicated that Ti-10Mo-5Fe revealed the highest compressive strength (2392 MPa) and strain (43%), and elastic modulus (91 GPa) low as compared to CP-Ti and some other Tibased alloys.…”
Section: Titanium and Its Alloys For Manufacturing Of Scaffoldsmentioning
confidence: 97%
“…However, to lower elastic modulus and minimal contents of toxic elements such as aluminum and vanadium, new biocompatible β-Ti alloys with β stabilizing alloying elements (Mo, Si, Ta, Sn, Zr) were recently developed. According to the literature, β-type Ti alloys demonstrate better mechanical properties, due to the moduli closer to those of human bone in comparison to α-type Ti alloys and α + β-type Ti alloys, as well as better biocompatibility due to the non-toxic nature of β-stabilizers [158]. For example, the elastic modulus of human cortical bone is about 30 GPa, while those of Ti-6Al-7Nb and Ti-6Al-4V are about 110 GPa and 112 GPa, and that of Ti-24Nb-4Zr-8Sn is below 50 GPa.…”
Section: Titanium and Its Alloys For Manufacturing Of Scaffoldsmentioning
confidence: 99%
“…The promising application of zirconium (Zr) is related to titanium-based alloys. Binary and ternary Ti-based alloys with zirconium, niobium, and tantalum are regarded as the most promising substitution of Ti64 for biomedical applications [ 84 ], showing significantly better biocompatibility and having mechanical properties much closer to those of human bones [ 16 , 17 , 85 , 86 , 87 , 88 ]. Growing demand for prostheses and implants and the ability of additive manufacturing to functionalize them will determine the demand for Zr as an alloying element rather than an individual material.…”
Section: Powder Materials Used For Additive Manufacturingmentioning
confidence: 99%